2015
DOI: 10.1039/c5cp00595g
|View full text |Cite|
|
Sign up to set email alerts
|

A practical approach to calculate the time evolutions of magnetic field effects on photochemical reactions in nano-structured materials

Abstract: A practical method to calculate time evolutions of magnetic field effects (MFEs) on photochemical reactions involving radical pairs is developed on the basis of the theory of the chemically induced dynamic spin polarization proposed by Pedersen and Freed. In theory, the stochastic Liouville equation (SLE), including the spin Hamiltonian, diffusion motions of the radical pair, chemical reactions, and spin relaxations, is solved by using the Laplace and the inverse Laplace transformation technique. In our practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For the analysis of the MFE observed by the time-resolved measurements, we first simulated time dependence of a population of the ground singlet state. The inverse Laplace transformation achieved by the Miller− Guy method 82. Then the time dependences of the fluorescence intensity were estimated by differentiations of the timedependence of the population of the ground singlet state.…”
mentioning
confidence: 99%
“…For the analysis of the MFE observed by the time-resolved measurements, we first simulated time dependence of a population of the ground singlet state. The inverse Laplace transformation achieved by the Miller− Guy method 82. Then the time dependences of the fluorescence intensity were estimated by differentiations of the timedependence of the population of the ground singlet state.…”
mentioning
confidence: 99%
“…It has been suggested and demonstrated that RP dynamics in the absence and presence of magnetic fields are rich in information not only regarding the mechanisms of MFEs but also regarding spatial RP motions in various media such as uniform solutions, , micelles, proteins, and ionic liquids. , Transient absorption spectroscopy, in which the absorption of transient radicals can be observed with high time resolution, is surely the first choice for the direct observation of RP dynamics under magnetic fields. In transient absorption measurements, however, the absorption of the photoexcited states, which are precursors of the radicals, is often overlapped with the absorption of the radicals.…”
Section: Introductionmentioning
confidence: 99%